ANALYSIS PT GOTO GOJEK TOKOPEDIA TBK FINANCIAL PERFORMANCE BEFORE AND AFTER IPO IN 2021 - 2024 - Nasution, Syarifuddin Hz; Novizar, Amelia (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to analyze the financial performance of PT GoTo Gojek Tokopedia Tbk (GOTO) during the period of 2021 to 2024 using a descriptive quantitative approach with profitability ratios as indicators, namely Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). The results show that GoTo experienced significant financial pressure after going public on the Indonesia Stock Exchange in April 2022, as indicated by increasing losses and declining operational efficiency. The NPM ratio recorded an extreme negative value of -612% in 2023 before improving significantly to -34% in 2024. Meanwhile, ROA and ROE also declined sharply in 2023 to -167% and -253%, respectively, but recovered in 2024 to -13% and -18%. Although all ratios remained in negative territory, the improving trend in the final year suggests that the company’s efficiency and profitability-focused strategies have begun to yield positive results in its financial performance.